PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR IPS DI SEKOLAH DASAR - Putri, Siska Melia; yunisrul, yunisrul; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the use of Jigsaw cooperative learning model on social studies learning outcomes in grade V SDN 11 Pahambat Balingka. This research is a quantitative research with the type of experimental research and quasi experimental research design. Sampling data was taken by using purposive sampling technique. The sample of this study was 45 students. The instruments used in collecting data are objective tests with multiple choice forms. The results of the calculation of the research data used are the t test, obtained obtained t count> t table that is 3.0995> 2.0167 with α = 0.05. Thus there is an effect of the use of Jigsaw cooperative learning model on student learning outcomes in social studies learning in the grade V of SD Negeri 11 Pahambat Balingka, Kecamatan IV Koto, Kabupaten Agam. Keywords: Jigsaw Cooperative, Student Learning Outcomes, IPS